2017
DOI: 10.1038/ajg.2016.542
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Eluxadoline in Patients with Irritable Bowel Syndrome with Diarrhea

Abstract: Objectives:Eluxadoline is a mixed μ-opioid receptor (OR) and κ-OR agonist and δ-OR antagonist, approved for the treatment of irritable bowel syndrome with diarrhea (IBS-D). This analysis evaluated the safety and tolerability of eluxadoline 75 and 100 mg twice daily (BID) in one Phase 2 (IBS-2001) and two Phase 3 (IBS-3001 and IBS-3002) studies.Methods:Adults with IBS-D (Rome III criteria) were randomized to placebo or eluxadoline (75 or 100 mg) BID for 12 (IBS-2001), 26 (IBS-3002), or 52 (IBS-3001) weeks. Safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(116 citation statements)
references
References 46 publications
3
110
0
3
Order By: Relevance
“…The adverse events of pancreatitis and sphincter of Oddi spasm (SOS), each in 0.3% of patients, led to specific exclusions of patients with a history of bile duct obstruction, pancreatitis, severe liver impairment or severe constipation, and in patients who drink more than three alcoholic beverages per day. An updated analysis of safety of eluxadoline in the phase II and III trials shows that clinically apparent SOS events were observed in eluxadoline-treated patients without a gallbladder, and the majority were observed with the higher (100 mg) dose of eluxadoline 100. Nevertheless, the FDA Adverse Event Reporting System received information on 99 cases of pancreatitis, 39 cases of SOS and 220 cases of abdominal pain within 10 months of the availability of the medication to patients with IBS-D 101…”
Section: Current Approaches To Manage Visceral Pain In Patients With Ibsmentioning
confidence: 99%
“…The adverse events of pancreatitis and sphincter of Oddi spasm (SOS), each in 0.3% of patients, led to specific exclusions of patients with a history of bile duct obstruction, pancreatitis, severe liver impairment or severe constipation, and in patients who drink more than three alcoholic beverages per day. An updated analysis of safety of eluxadoline in the phase II and III trials shows that clinically apparent SOS events were observed in eluxadoline-treated patients without a gallbladder, and the majority were observed with the higher (100 mg) dose of eluxadoline 100. Nevertheless, the FDA Adverse Event Reporting System received information on 99 cases of pancreatitis, 39 cases of SOS and 220 cases of abdominal pain within 10 months of the availability of the medication to patients with IBS-D 101…”
Section: Current Approaches To Manage Visceral Pain In Patients With Ibsmentioning
confidence: 99%
“…In the phase II and III clinical trials of eluxadoline, 10 events consistent with SOS occurred in patients treated with eluxadoline; 8 in the 100 mg group (0.8%) and 2 in the 75 mg group (0.2%). 18 All SOS events occurred in patients without a gallbladder. A total of 8 of the 10 patients with SOS presented with abdominal pain and elevated aminotransferases; 7 in the 100 mg group (0.7%) and 1 in the 75 mg group (0.1%).…”
Section: Safetymentioning
confidence: 98%
“…60 This was confirmed in a more recent study of nearly 2000 patients with IBS-D with 10 patients developing sphincter of Oddi spasm, most at the higher eluxadoline dose of 100mg. 61 In a recent communication (https://www.fda.gov/Drugs/DrugSafety/ucm546154.htm), the U.S. Food and Drug Administration (FDA) issued a warning that eluxadoline should not be used in patients who do not have a gallbladder. An FDA review found these patients have an increased risk of developing serious pancreatitis that could result in hospitalization or death.…”
Section: μ Opioids Gi Symptoms and Syndromesmentioning
confidence: 99%